REALIZATION OF THE TRANSLATION OF HÄTTE AND WÄRE IN CORNELIA FUNKE’S NOVEL TINTENTOD - Fanidya Hikhmatus Syiam; Sufriati Tanjung (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2020)
REALIZATION OF THE TRANSLATION OF HÄTTE AND WÄRE IN CORNELIA FUNKE’S NOVEL TINTENTOD Abstract:  The subjunctive mood in german language (Konjunktiv II) is a complex grammatical phenomenon. The problem at that phenomenon has become more interesting in the translation field. Especially if the language pair is Bahasa Indonesia because there are many ways to express the german subjunctive mood in Bahasa Indonesia. The Indonesian language has a lot of word preferences with various meanings, which must be noticed carefully. This study aims to identify the Konjunktiv II sentence which used most common past subjunctive verbs hätte and wäre, to categorized and described Konjunktiv II sentences based on their functions. This research used descriptive qualitative. The data were the Konjunktiv II sentence collected from the fantasy novel Tintentod and their translation in Bahasa Indonesia. The data were collected through observations and note-taking techniques. The analysis technique was translational. The research results as fellows (1) there is a 418 Konjunktiv II sentence in Tintentod novel. (2) 47,4% of Konjunktiv II sentences are included in irregular Vergleichssatz categories. The translator knowledge and awareness about Konjunktiv II categories needed to achieve equivalence in subjunctive mood’s meaning.Keywords: Konjunktiv II forms, Konjunktiv II functions, Subjunctive mood, TranslationREALISASI PENERJEMAHAN HÄTTE DAN WÄRE DALAM NOVEL TINTENTOD KARYA CORNELIA FUNKEAbstrak:  Modus subjungtif dalam bahasa Jerman (Konjunktiv II) merupakan suatu fenomena gramatikal yang kompleks. Dalam penerjemahan kalimat Konjunktiv II ke dalam bahasa Indonesia dapat ditemui berbagai pilihan kata sebagai padanan bagi bentuk tersebut. Pilihan-pilihan itu tentu mengandung berbagai variasi makna yang perlu diperatikan dengan teliti. Tujuan penelitian ini adalah mengidentifikasi hasil penerjemahan bentuk Konjunktiv II yang disusun dengan verba hätte dan wäre. Penelitian ini juga bertujuan mengklasifikasikan bentuk Konjunktiv II sesuai fungsinya serta mendeskripsikan bentuk kalimat terjemahannya di dalam bahasa Indonesia. Penelitian ini merupakan penelitian deskriptif kualitatif. Data pada penelitian ini berupa kalimat berkonstruksi Konjunktiv II serta kalimat hasil penerjemahannya. Pengumpulan data dilakukan menggunakan teknik simak dan catat dengan teknik analisis padan translasional. Berdasarkan analisis ditemukan bahwa Pertama, terdapat 418 kalimat Konjunktiv II di dalam novel Tintenod. Kedua, Paling sering ditemukan kalimat berkategori irrealer Vergleichssatz yakni 47,4%. Ketiga, untuk menerjemahkan kalimat Konjunktiv ke dalam bahasa Indonesia perlu diperhatikan kesesuaian elemen-elemen pembentuk kalimat serta kesadaran bahwa terdapat perbedaan antara kalimat pengandaian dan perumpamaan dan beragam fungsi spesifik penggunaan bentuk Konjunktiv bahasa Jerman. Kata kunci: Bentuk Konjunktiv II, Fungsi Konjunktiv II, Modus subjungtif, Penerjemahan